Views on Language Acquisition, General Achievement in Language Acquisition, and Socioeconomic Status: A Correlational Study - Dewi, Anita Candra; Asrifan, Andi; Lulaj, Enkeleda; Mohamed, Sheik (Yayasan Corolla Education Centre, 2024)
This research aims to better understand the interplay between Indonesian students' socioeconomic background, their views on the efficacy of language instruction, and the overall results of their language classes. This study aimed to achieve that goal by including 350 undergraduate students from Universitas Muhammadiyah Sidenreng Rappang who were taking English-language courses. Based on their socioeconomic status, they were categorized. In response to a questionnaire, they shared their views on the best ways to acquire a second language in various linguistic settings. To ensure that all participants were on the same page in terms of their overall level of proficiency or the results of their language study, they were also given a practice test of the TOEFL exam. Descriptive statistics, factor analysis, and other parametric statistical tests were applied to the quantitative data. The results showed that the students' socioeconomic position had a positive correlation with the overall language learning outcome. In addition, the results showed that the participants' ideas about language learning had a significant impact on their language learning outcomes. The results suggest that both the rate of language acquisition and the likelihood of measurement errors can be improved provided language instructors have the information they need to help their students overcome negative beliefs.